Species diversity of Charales in Transcarpathian Region - Borysova, O.V.; Gromakova, A.B.; Burova, O.V. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2023)
The results of the study on charophytes (Charales, Charophyta) of different water bodies of the Transcarpathian Region, carried out in 2016–2023, critical study of herbarium material collected in 1961–2013 and summarized published information are presented. The current state of the species diversity of the Transcarpathian Region charophytes, represented by seven species (78% of the total number of the Ukrainian Carpathians Charales) belonging to the genera Chara L. (C. braunii C.C. Gmelin, C. contraria A. Braun ex Kütz., C. globularis Thuill., C. virgata Kütz. and C. vulgaris L.) and Nitella C. Agardh (N. flexilis (L.) C. Agardh, N. mucronata (A. Braun) Miq.) is given and analyzed. Among them N. mucronata is a new species for the Transcarpathian Region. It is shown that geographically, most species of Transcarpathian Region have a cosmopolitan, subcosmopolitan or Holarctic type of arial. Overall, 14 locations of charophytes species revealed during the floristic research. According to a frequency of occurrence, the species are denoted as most common for Transcarpathian Region (C. globularis), frequent (N. mucronata), rare (C. virgata, C. vulgaris, N. flexilis) and endangered (C. braunii, C. contraria). It is suggested that main factors influencing on diversity and distribution of Charales in Transcarpathian Region are the type of water bodies, a degree of mineralization, as well as chemical composition of main ion and active reaction (pH) of water. A comparison study of the species diversity of Charales of Transcarpathian region with that of Lviv, Ivano-Frankivsk and Chernivtsi regions within the Carpathian-Danube algofloristic subprovince revealed certain originality of all studied regions. The obtained data is substantial contribution in the investigation on Charales of the Ukrainian Carpathians in general.